Outcomes of Alcohol Septal Ablation in the Patients with Hypertrophic Obstructive Cardiomyopathy - Cai, Mei-lian; Chen, Yu-ming; Zhong, Guo-qiang (Cardiology and Cardiovascular Medicine, 2024)
Background: Alcohol septal ablation (ASA) is a commonly used invasive procedure for reducing septum volume in patients with hypertrophic obstructive cardiomyopathy (HOCM). Objective: This study aimed to evaluate the safety and efficacy of ASA in patients with drug-refractory symptomatic HOCM. A total of 20 patients hospitalized in the Department of Cardiology at our hospital with HOCM from July 2019 to July 2022 were collected and received ASA to compare the differences in the relevant indicators before ASA and 3 months after ASA. Results: At 3 months post-ASA, mean of left ventricular outflow tract (LVOT) peak gradient decreased to 55.5%±18.5%. Echocardiography derived that LVOT peak gradient decreased from 88.1±32.0 mmHg to 40.4±28.7 mmHg (p<0.001). Interventricular septum thickness (IVST) reduced from 21.8±5.4 mm to 16.6±4.5 mm (p<0.001). Left ventricular outflow tract diameter (LVOTD) increased from 7.6±2.7 mm to 11.5±2.4 mm (p<0.001). Mitral valve instantaneous regurgitation (MVIR) decreased from 8.5±6.1 mL to 4.7±3.2 mL (p<0.001). There were no significant differences in left ventricular end-diastolic diameter (LVEDD) or left ventricular ejection fraction (LVEF) (P>0.05). During ASA and up to 3 months post procedure, no serious complications were observed. Conclusion: ASA has been a safe and effective treatment strategy for patients with drug-refractory symptomatic HOCM.